Blockchain in real estate: Recent developments and empirical applications. (October 2022) - Saari, Anniina; Vimpari, Jussi; Junnila, Seppo
Abstract: The real estate sector is often presented as an exemplary field that benefits from practical blockchain applications. The general hypothesis is that, in theory, blockchain could solve some significant challenges the real estate sector is facing, such as nontransparency, inefficiencies, fraud and corruption, high costs, and trust issues. However, the literature focuses on blockchain's theoretical benefits, challenges, or concepts. This research aims to understand the recent developments in the blockchain literature, specifically in the real estate sector, and to understand the current real-world applications by collecting empirical evidence from blockchain studies. The systematic literature review identified 262 relevant documents, after which a thematic content analysis was performed. Conceptual blockchain literature was identified to propose blockchain benefits for the real estate sector in four categories: land administration, real estate transactions, tokenization, and real estate management. The thematic content analysis also identified 26 empirical applications, of which all except one were related to land administration. Although the conceptual and theoretical blockchain literature presents blockchain as a disruptive and transformative technology for the real estate sector, the empirical applications suggest that blockchain adoption materializes more in hybrid, smaller-scale settings, where blockchain is merely an add-on layer to existing systems. Overall, most of the conceptual blockchain benefits remain empirically unconfirmed. On the other hand, the empirical applications suggest that blockchain could, for example, increase efficiency, reduce time, and provide verifiability, transparency, and automation, even in smaller-scale, hybrid settings. In addition, the applications indicate that blockchain could, in some cases, help reduce fraud and increase security and trust compared with centralized digital solutions. Finally, the empirical insights emphasize the role of political will, regulatory framework, availability of reliable digital data, public–private partnerships, and educational aspects in blockchain applications. Highlights: A systematic review of 262 documents uncovers real-life blockchain applications in the real estate sector. Provides empirical insights on the theoretical blockchain benefits and challenges for the real estate sector. Current adoption concentrates in land administration, is small in scale, and usually an add-on layer to existing systems. Current applications seem to supply some benefits. Most of the theoretical blockchain ideas remain empirically unconfirmed.